Stosowanie zabiegów fizjoterapeutycznych u osób uprawiających balet po urazie sportowym oraz przeciążeniach narządu ruchu = The use of physical therapy in people practicing ballet trauma and sports overload the musculoskeletal system - Magdalena Michalczak; Katarzyna Bojarczuk; Agata Smoleń (Kazimierz Wielki University, 2016)
Michalczak Magdalena, Bojarczuk Katarzyna, Smoleń Agata. Stosowanie zabiegów fizjoterapeutycznych u osób uprawiających balet po urazie sportowym oraz przeciążeniach narządu ruchu = The use of physical therapy in people practicing ballet trauma and sports overload the musculoskeletal system. Journal of Education, Health and Sport. 2016;6(7):640-651. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60867 http://ojs.ukw.edu.pl/index.php/johs/article/view/3783       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     Stosowanie zabiegów fizjoterapeutycznych u osób uprawiających balet po urazie sportowym oraz przeciążeniach narządu ruchu The use of physical therapy in people practicing ballet trauma and sports overload the musculoskeletal system   Magdalena Michalczak, Katarzyna Bojarczuk, Agata Smoleń   Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych Uniwersytetu Medycznego w Lublinie       Słowa kluczowe: przeciążenie tkanek, balet, urazy sportowe. Keywords: overload tissue, ballet, sports injuries.     Streszczenie   Wprowadzenie: Każdy sportowiec poddawany jest obciążeniom. Są to obciążenia psychiczne i fizyczne i wzajemnie ze sobą powiązane. Zmiany stanu wytrenowania i poziomu formy sportowej, a także rozwój sportowy zawodnika to efekt długotrwałych zmian adaptacyjnych w organizmie człowieka pod wpływem treningu. Cel pracy: Ocena jakie zabiegi fizjoterapeutyczne najczęściej stosowane były u pacjentów po przebytym urazie sportowym Materiał i metody: Analizę przeprowadzono na losowo wybranych respondentach z grupy wiekowej od 12 do 38 roku życia, zamieszkałych na terenie województwa lubelskiego. Łącznie badaniem objęto grupę 20 osób. Wyniki: Proces patologii tkanek i urazów sportowych dotyczy 90% ankietowanych. 90% ankietowanych trening zawsze rozpoczyna od rozgrzewki, natomiast 10% badanych odpowiedziało, że czasami nie rozpoczynają treningu od rozgrzewki. Rehabilitacji po przeciążeniu tkanek objętych było 75%, przy czym w przychodni ambulatoryjnej rehabilitowanych jest 60% ankietowanych. W mniejszym stopniu pacjenci korzystają z usprawniania w domu - 10%  badanych. Najczęściej stosowanym zabiegiem była kinezyterapia - 75%. Masaż leczniczy również został uznany za często stosowany zabieg w patofizjologii tkanek - 15%. Rzadziej stosowanymi zabiegami okazały się prądy galwaniczne - 5% oraz ultradźwięki - 5%. U znacznej większości osób ankietowanych - 75% nie występowały choroby współistniejące. Wnioski: W badaniach stwierdzono wysoki odsetek osób, u których występują przeciążenia tkanek oraz urazy stawów, które spowodowane są zbyt częstym i długotrwałym treningom - 90% badanych. U znacznej większości osób badanych nie występowały choroby współistniejące, które mogłyby dodatkowo wpływać na powstawanie urazów tak jak np. osteoporoza - 75% osób ankietowanych.         Summary   Introduction: Every athlete is subjected to loads. These are the mental and physical load and interrelated. Changes in the level of training and sports form, as well as the development of a sports player is the result of long-term adaptive changes in the human body under the influence of training. Aim: To what physiotherapy treatments most commonly been used in patients with a history of trauma sports Material and Methods: The analysis was conducted on randomly selected respondents from the age group of 12 to 38 years of age, residing in the Lublin province. In total, the study involved a group of 20 people. Results: The process of pathology and tissue sports injuries applies to 90% of respondents. 90% of respondents training always starts with a warm-up, while 10% of respondents answered that they sometimes do not start training warm-up. Rehabilitation after overload tissues were covered by 75%, while in outpatient rehabilitation clinic is 60% of the respondents. To a lesser extent, patients benefit from the improvement in the home - 10% of respondents. The most commonly used procedure was physiotherapy - 75%. Therapeutic massage has also been recognized as a frequently used treatment in the pathophysiology of tissue - 15%. Less commonly used treatments proved to galvanic currents - 5%, and ultrasound - 5%. The vast majority of respondents - 75%, there were no comorbidities. Conclusions: The study found a high percentage of people who experience an overload of tissue and joint injuries, which are caused by too frequent and prolonged workouts - 90% of respondents. The vast majority of the subjects did not occur concomitant diseases, which could further affect the formation of injuries such as, eg. Osteoporosis - 75% of the polled.